ANALYSIS OF THE SUSTAINABILITY OF THE UTILIZATION OF THREADFIN BREAM (Nemipterus sp.) LANDED AT LEMPASING FISHING PORT, BANDAR LAMPUNG - Putriani, Rizha Bery; Lahay, Almira Fardani; Putri, Septi Malidda Eka; Julian, David (Jurusan Perikanan dan Kelautan, 2024)
The waters of Lampung Bay have high potential resources for threadfin bream (Nemipterus sp.). This fish has significant economic value as a diverse food ingredient. However, currently, the body size of threadfin bream found tends to be uniform and even smaller due to continuous overfishing. The research was conducted to assess the status of utilization of threadfin bream resources in the waters of Lampung Bay based on five important aspects, namely ecology, economics, social, technological and institutional. The research was carried out in May 2023 at Lempasing Fishing Port, Bandar Lampung City, with data collection through observation and interviews. Data analysis used the multi-dimensional scaling (MDS) method using the Rapfish (rapid appraisal for fisheries) application to evaluate the sustainability of the use of threadfin bream. The results of the analysis show that the sustainability index value for the use of threadfin bream in the waters of Lampung Bay is as follows: ecological dimension 48.59; economic dimension 36.80; social dimension 75.00; technology dimension 49.91; and ethical dimension 61.64. Based on these results, it can be concluded that the use of threadfin bream in the waters of Lampung Bay is quite sustainable, with an average index value of 54.39.Keywords: Ecological dimension, multi-dimensional scaling, Rapfish, sustainability index.